Law No. 172 of the Year 2018 Amending the Provisions of the Customs Law Promulgated by Law No. 66 of the Year 1963 = قانون رقم 172 لسنة 2018 بتعديل أحكام قانون الجمارك الصادر بالقانون رقم 66 لسنة 1963 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic